The Shaheen Bagh Strike: Muslim Women and Political Protest in Contemporary India - Moumita Biswas (Atlantis)
The Shaheen Bagh protest in New Delhi highlighted the changing dynamics of Muslim women’s participation in socio-political movements in India. This paper argues how Muslim women proved themselves to be concerned citizens while protesting against the Citizenship Amendment Act (2019) and other forms of social discrimination. The paper analyses the Shaheen Bagh protest from an intersectional perspective to understand how Muslim women voiced their political opinions negotiating with gender and religion-based discrimination; they had to fight the multiple forms of patriarchy of Indian society while protesting against hypermasculine Hindutva politics. The Shaheen Bagh protest can be called a feminist strike of Third World women for the rights of their religious community in a particular socio-political context.